Effect of MWCNTs on microstructure and properties of WC-9Co gradient cemented carbides. Issue 13 (1st July 2022) - Jiang, Junpeng; Ouyang, Shuilin; Chen, Hao; Guo, Shengda; Yin, Lei; Tan, Zhuopeng; Shi, Haidong; Zhong, Zhiqiang; Qiu, Lianchang
Abstract: WC-9Co-xMWCNTs (Multiwalled carbon nanotubes) gradient cemented carbides with cubic carbides free layer (CCFL) were prepared by powder metallurgy method. The effect of different MWCNTs content on the microstructure and mechanical properties of WC-9Co gradient cemented carbides have been studied. The microstructure and phase composition of WC-9Co-xMWCNTs composites were characterized by means of optical microscope, scanning electron microscopy (SEM) and X-ray diffraction (XRD). In addition, the hardness, fracture toughness, bending strength and friction coefficients were tested by Vickers indenter, universal testing machine and tribometer. The results showed that the MWCNTs could promote the growth of CCFL. The minimum grain size of WC was obtained in the WC-9Co-0.08 wt% MWCNTs composites and the sample possessed the highest hardness and bending strength, the lowest friction coefficient and the best wear resistance at the same time. The fracture toughness and relative density increased steadily together with the addition of MWCNTs. Besides, the mechanism of MWCNTs enhancing the alloys include bridge connection, crack deflection, pull-out and strengthening effect of the network structure.